An overview of the Ephydridae (Diptera) of Saudi Arabia - Dawah, Hassan A.; Ahmad, Syed K.; Abdullah, Mohammed A.; Zatwarnicki, Tadeusz (Zootaxa, 2019)
Despite the species richness of Ephydridae world-wide (2000 species) and its prominent environmental roles as a minor pest and as a food for wildlife, only 13 species have been recorded from Saudi Arabia. Between 2012 and 2016, a biodiversity study of Diptera was conducted at Jazan, Asir, and Najran in south-western Saudi Arabia, at 22 sites, was performed mainly using Malaise traps and sweep nets. In this study, 43 known species of Ephydridae were identified, 37 of them for the first time from southwestern Saudi Arabia and 16 from Arabian Peninsula. This brings the total number of Ephydridae species in Saudi Arabia to 49 (including previous records). There were a further four species, which could not be identified authoritatively to species level. A list of all species of Ephydridae recorded from Saudi Arabia is appended. Images of thirty-two species are presented. The species recorded in this study are more Palaearctic in origin as compared to other regions. Biological information (where known) and world-wide distribution are included. This study has added new records to the Saudi Arabian checklist of Ephydridae, which will provide the basis for systematic studies and fauna analyses of future work on the family. The need for further field and laboratory work and surveillance is highlighted.